Parent Perspectives on Family-Centered Pediatric Electronic Consultations: Qualitative Study - Verma, Rhea; Krishnamurti, Tamar; Ray, Kristin N (JMIR Publications, 2020)
BackgroundElectronic consultations, which use store-and-forward transfer of clinical information between a primary care physician and a specialist, improve access to specialty care. Adoption of electronic consultations is beginning in pediatric health care systems, but little is known about parent perspectives, informational needs, and preferences for interaction with this new model of care. ObjectiveThis study aimed to examine parent perspectives about electronic consultations, including perceived benefits and risks, anticipated informational needs, and preferences for parent engagement with electronic consultations. MethodsWe recruited caregivers of pediatric patients (aged 0-21 years) attending visits at an academic primary care center. Caregivers were eligible if their child had ever been referred for in-person specialty care. Caregivers participated in a semistructured interview about electronic consultations, including general perspectives, desired information, and preferences for parental engagement. Interviews were transcribed and qualitatively analyzed to identify parent perspectives on electronic consultations in general, information parents would like to receive about electronic consultations, and perspectives on opportunities to enhance parent engagement with electronic consultations. ResultsInterviewees (n=20) anticipated that electronic consultations would reduce the time burden of specialty care on families and that these had the potential to improve the integrity and availability of clinical information, but interviewees also expressed concern about data confidentiality. The most detailed information desired by interviewees about electronic consultations related to data security, including data confidentiality, availability, and integrity. Interviewees expressed concern that electronic consultations could exclude parents from their child's health care decisions. Interviewees saw value in the potential ability to track the consultation status or to participate in the consultation dialogue, but they were more ambivalent about the idea of read-only access to consultation documentation. ConclusionsParents identified the potential risks and benefits of pediatric electronic consultations, with implications for communication with families about electronic consultations and for incorporation of features to enhance parent engagement.